Evaluation of the ability of lines of trees to trap tsunami flotsam. Issue 3 (3rd July 2018) - Imai, Kentaro; Hayashi, Akihiro; Imamura, Fumihiko
ABSTRACT: Following the 2011 Tohoku earthquake, coastal forests dissipated the energy of the tsunami and trapped flotsam. Although studies have shown how trees dissipate flow energy and are damaged in the process, the factors determining the trapping of flotsam by lines of trees or their capacity to do so have not been quantitatively examined. Quantitative evaluation of these factors may lead to tree-based strategies for suppressing the secondary damage caused by tsunami flotsam. To increase the ability of trees to mitigate damage, their physical limitations need to be identified. Field surveys revealed that integrated clusters of flotsam were caught by trees even if individual floating objects were smaller than the distance between the trees. Hydraulic experiments revealed relations between physical factors and the capture of flotsam. From these relations, we derived a simple formula for evaluating the trapping capacity of lines of trees. The estimates from our model were consistent with the actual results of the 2011 tsunami in Tagajo city, Miyagi prefecture, where trees did not topple under the forces applied by trapped flotsam.